ENERGY AND ECONOMIC COMPARATIVE STUDY OF A TRACKING VS. A FIXED PHOTOVOLTAIC SYSTEM - Petros J. Axaopoulos; Emmanouil D. Fylladitakis (European Scientific Journal, ESJ, 2013)
In this study the performance of a two-axis tracking system is compared to that of an identical fixed inclination system facing south at optimal annual inclination angle. The study was performed in three locations across Europe; Athens in Greece, Stuttgart in Germany and Aberdeen in UK, characterized by different climatic conditions. The monthly and annual energy output of a real world small scale electricity generation photovoltaic installation with a rated power of 6.4kWp has been calculated, taking into account all electrical and temperature losses, as well as the power consumption of the two axis tracker which has been deducted from the annual generation of the system. For each geographic location the optimal annual inclination angles were calculated correlated to the latitude of the location. Finally, an economic analysis based on current economic data and local legislation has been performed and economic analysis diagrams are being presented to help evaluate any future changes of the feed-in tariff rates and capital cost, as well as possible feed-in tariff rate and capital cost subsidies. This study determines that investing on grid connected photovoltaic systems critically depends not only on the area’s climatic conditions but also on the national legislation and regional energy prices.